Computational Modeling for Industrial-Organizational Psychologists - Vancouver, Jeffrey B.; Wang, Mo; Weinhardt, Justin M. (SIOP Organizational Frontiers Series, 2024)
Computational Modeling for Industrial-Organizational Psychologists; Jeffrey B. Vancouver; Mo Wang; Justin Weinhardt; Jeffrey Vancouver; SIOP Organizational Frontiers Series; SIOP; Society for Industrial and Organizational Psychology; SIOP Organizational Frontiers; computational modeling; computerational models; I/O psychology; vocational psychology; work psychology; organizational psychology; human resource management; organizational behavior; organizational science